DISTRIBIÇÃO GEOGRÁFICA E AUTOECOLOGIA DE MORCEGOS HEMATÓFAGOS Diaemus youngi (Jentik, 1893) E Diphylla ecaudata (Spix, 1823) (MAMMALIA: CHIROPTERA) NOS BIOMAS BRASILEIROS - DIAS, Rivael Rocha; DIAS, Rosa Maria; PEREIRA DA SILVA, Elifas Augusto; ORTÊNCIO-FILHO, Henrique; KASHIWAQUI, Elaine Antoniassi Luiz (ANAIS DO ENIC, 2025)
.